Dysglycemia associated with quinolones. Issue 3 (June 2015) - El Ghandour, Sarah; Azar, Sami T.
Highlights Hyperglycemia and hypoglycemia are associated with antimicrobials use. Fluoroquinolones is the most reported to cause dysglycemia. Mechanisms explaining dysglycemia are discussed.